A study on earthquake design consideration Malaysian bridge for foundation / Sarina Salleh - Salleh, Sarina (Faculty of Civil Engineering, 2006)
The objectives of the study are to analyse the earthquake design consideration for Penang Bridge foundation, Johor Bahru-Singapore Second Link foundation and Penang Butterworth Outer Ring Road (BORR) foundation and to compare the foundation of the bridges with earthquake induced failed bridges overseas and to suggest future area of study for Malaysian earthquake foundation design. The study involved collection of data from completed bridges such as Penang Bridge, BORR and Second Link. Based on the data collected potential area of study identified are effect of soil type, Peak Ground Acceleration (PGA) for the area and suitable pile protection.